Akurasi Mid Upper Arm Circumference (MUAC) dalam Mendeteksi Malnutrisi Akut pada Anak di bawah 5 Tahun : A Literature Review: Tinjauan Literatur : Akurasi MUAC dalam Mendeteksi Malnutrisi Akut - Ariza, Nahya Rahmatul; Siti Rahayu; Willmart, Auresa Caesarputriaulya (Amerta Nutrition, 2023)
Background: Fast and accurate detection of acute malnutrition is important to prevent death. The use of Mid Upper Arm Circumference (MUAC) can be an alternative but its accuracy is still being explored because many differences in research results are found. Objectives: This literature aimed to identify the accuracy (sensitivity and specificity) and optimal MUAC cut-off in detecting acute malnutrition in children under 5 years. Methods: Search for articles using Google Scholar and Pubmed with the keywords "MUAC” "children” "acute malnutrition”. Selection based on the question "How is the sensitivity and specificity of MUAC in detecting acute malnutrition in children under 5 years” with inclusion criteria articles for the last 10 years, fully accessible and free of charge. Excluding non-English articles and type review articles. Six articles were found that further review. Discussion: The sensitivity of the MUAC indicator by World Health Organization in detecting acute malnutrition is smaller than its specificity. The lowest sensitivity of MUAC in detecting severe (<11.5 cm) and moderate (11.5-12.5 cm) acute malnutrition is in Nepal, namely 13.6% and 21% respectively. Based on the results of analysis using the ROC curve in each article, it was found that the optimal MUAC cut-off varied in detecting cases of acute malnutrition. Conclusions: The MUAC cut-off accuracy recommended by the World Health Organization to identify severe and moderate acute malnutrition is not optimal. Therefore, further studies are needed in each country to determine the optimal cut-off that is appropriate for the region according to the age group and problem classification.